PERAN MEDIA QUIZIZZ DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the role of Quizizz as a learning media in improving students' learningmotivation. The research employed a qualitativemethod with a literature review approach. Data were collected from various sources such as books, scientific journals, and research articles related totechnology-based learning media and studentmotivation. The data collection technique used contentanalysis, while data analysis was carried out byreviewing, comparing, and synthesizing informationfrom the selected literature. The results of the study indicate that Quizizz plays a significant role in enhancing students' learning motivation. This isreflected in increased student engagement during thelearning process, a more interactive and enjoyablelearning environment, and higher enthusiasm in participating in learning activities. Additionally, featuresin Quizizz such as real-time feedback, rankingsystems, and attractive visual displays encouragestudents to be more active and motivated in learning.In conclusion, the use of Quizizz as a technology-based learning media can serve as an effectivealternative in improving students' learning motivation. This media not only supports the evaluation processbut also creates a more meaningful and innovativelearning experience.